Immunization of mice with plasmid DNA encoding hepatitis B virus core antigen (HBcAG) - Bulut, Yasemin; Bulut, Hakan; Doymaz, Mehmet Ziya (My University, 2003)
The aim of this study was to investigate the antibody response following immunization with plasmid vector DNA containing the hepatitis B virus core antigen (HBcAg) gene of a hepatitis B virus (HBV) isolated from a patient in Turkey. A HBcAg gene fragment was cloned into a pcDNA 3 eukaryotic expression vector. After confirmation of the cloning of the HBcAg gene, the expressing vector based HBcAg was used in DNA immunization experiments. Four-to 6-week-old Balb/c mice were immunized with HBcAg expressing plasmids and the anti-HBcAg antibody responses of the mice were evaluated by enzyme immunoassay (EIA). The results of this study indicated that HBcAg expressed from pcDNA 3 based eukaryotic expression vector induced an anti-HBcAg response when introduced intramuscularly into Balb/c mice.
Keywords: Core antigen; DNA immunization; Hepatitis B virus